2023
DOI: 10.1212/wnl.0000000000207579
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Dental Health With the Progression of Hippocampal Atrophy in Community-Dwelling Individuals

Abstract: Background and ObjectivesAlthough tooth loss and periodontitis have been considered risk factors for Alzheimer's disease, recent longitudinal researches have not found a significant association with hippocampal atrophy. Therefore, this study aimed to clarify a longitudinal association between the number of teeth present (NTP) and hippocampal atrophy dependent on the severity of periodontitis in a late middle-aged and older adult population.MethodsThis study included community-dwelling individuals aged ≥55 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“… 25 Human periodontitis patients with a greater number of teeth have been observed to experience a faster rate of hippocampal atrophy and cognitive decline. 26 However, the exact cells in the hippocampus affected by periodontitis remain to be identified. In the present study, we constructed a comprehensive single-nucleus transcriptomic atlas of the hippocampus using snRNA-seq.…”
Section: Discussionmentioning
confidence: 99%
“… 25 Human periodontitis patients with a greater number of teeth have been observed to experience a faster rate of hippocampal atrophy and cognitive decline. 26 However, the exact cells in the hippocampus affected by periodontitis remain to be identified. In the present study, we constructed a comprehensive single-nucleus transcriptomic atlas of the hippocampus using snRNA-seq.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, AD patients exhibit an increased risk of tooth loss and complete edentulism, surpassing the risks observed within the general population ( 21 ). A prospective cohort study has revealed a longitudinal association between the number of teeth present (NTP) and hippocampal atrophy, particularly when considering the severity of periodontitis, and this underscores the potential link between tooth loss and subsequent cognitive decline, which may outweigh the influence of age ( 22 ). Moreover, the loss of functional teeth and impairment of functional occlusal units can further exacerbate cognitive impairments in affected individuals ( 23 ).…”
Section: The Relationship Between Oral Microbiota and Admentioning
confidence: 99%
“…However, a long-term follow-up study was carried out on individuals participating in the National Health and Nutrition Examination Survey III (NHANES III) from 1988 to 2019. The results indicated that the IgG antibody cluster of periodontal microbiota could not serve as a predictor for AD mortality ( 22 ). Additionally, a prospective longitudinal study has indicated that elevated levels of TNF-α in the blood plasma, as well as the presence of antibodies against periodontal pathogens, may be associated with the development or progression of AD, and these factors may contribute to improving the clinical diagnosis of AD ( 50 ).…”
Section: The Potential Application Of Oral Microbiota In the Preventi...mentioning
confidence: 99%
“… 44 To date, there are few reports that analyzed features of periodontitis and brain imaging findings associated with impaired cognition and ADRD. 21 , 45 , 46 , 47 , 48 , 49 , 50 In this study, we examined the association of clinical, microbiological, and serological markers of periodontitis with magnetic resonance imaging (MRI) markers of atrophy and cerebrovascular disease in a tri‐ethnic cohort of individuals over the age of 65 years.…”
Section: Introductionmentioning
confidence: 99%